Synthesis of α‐Amino‐γ‐lactams through Pd‐Catalzed Intramolecular Allylic Alkylation of Sarcosine Allyl Amides. Issue 8 (14th January 2014) - Thies, Sarah; Kazmaier, Uli
Abstract: N ‐Protected amino acid allyl amides with an allylic leaving group can be used as substrates in palladium‐catalyzed allylic alkylation. Whereas intermolecular allylations proceed with excellent yields under standard conditions for enolate reactions, the intramolecular version is not a trivial issue. N ‐Protected glycine amides preferentially form piperidinones through N ‐allylation, but the corresponding sarcosine derivatives provide γ‐lactams in acceptable to good yields in dichloromethane, especially when the corresponding titanium enolates are formed. Abstract : Titanium enolates generated from N ‐protected sarcosyl allyl amides with an allylic leaving group undergo palladium‐catalyzed intramolecular allylic alkylations in dichloromethane, giving rise to amino‐functionalized γ‐lactams in an acceptable diastereoselective fashion.